2005
DOI: 10.1080/09670870500179698
|View full text |Cite
|
Sign up to set email alerts
|

Relationships betweenOstrinia nubilalis(Lepidoptera: Crambidae) feeding activity, crop technique and mycotoxin contamination of corn kernel in northwestern Italy

Abstract: The relationships between the feeding activity of Ostrinia nubilalis (Hü bner), crop technique (i.e., planting date, nitrogen fertilization, irrigation, and use of deltamethrin), and mycotoxin contamination of kernels were studied in Italian corn crop systems. Field sampling was conducted to determine the incidence of first-and second-generation larvae for each crop technique. At harvest, kernel contamination by fumonisins and zearalenon was measured and related to the number and position of tunnels on corn ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 28 publications
4
31
2
Order By: Relevance
“…At present, pyrethroid treatment applied after the first generation ECB flight peak is normal practice for farmers in Northern Italy, since they usually spray when adult catches decline, after the peak has been reached. In our experiments, the efficacy in reducing fumonisin contamination observed with pyrethroid application at approximately 7 days after the ECB flight peak was between 26 and 54%, confirming values observed in previous studies (Alma et al 2005;Saladini et al 2008;Blandino et al 2008a). Considering the greater efficacy in reducing fumonisin content observed in this study with earlier applications, it can be stated that the timing of chemical treatment needs to be reconsidered.…”
Section: Food Additives and Contaminants 1511supporting
confidence: 93%
See 2 more Smart Citations
“…At present, pyrethroid treatment applied after the first generation ECB flight peak is normal practice for farmers in Northern Italy, since they usually spray when adult catches decline, after the peak has been reached. In our experiments, the efficacy in reducing fumonisin contamination observed with pyrethroid application at approximately 7 days after the ECB flight peak was between 26 and 54%, confirming values observed in previous studies (Alma et al 2005;Saladini et al 2008;Blandino et al 2008a). Considering the greater efficacy in reducing fumonisin content observed in this study with earlier applications, it can be stated that the timing of chemical treatment needs to be reconsidered.…”
Section: Food Additives and Contaminants 1511supporting
confidence: 93%
“…The second generation larvae, in particular, plays an important role in the epidemiology of F. verticillioides in maize (Sobek and Munkvold 1999) and insect damage of ears can increase fumonisin contamination of kernels (Logrieco et al 2003). In maize grain, ECB feeding activity is crucial in fumonisin contamination: damaged ears suffer a 40 times higher contamination rate than healthy ears (Alma et al 2005). Several studies have established that the control of ECB clearly affects fumonisin levels in maize kernel at harvest.…”
Section: Management Of Fumonisin Contamination In Maize Kernels Throumentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is known that crop growing techniques such as planting date, irrigation, nitrogen fertilization, or damage by insects and inappropriate storage can contribute to fungal growth on kernels (Shelby et al 1994;Pascale et al 1997;Avantaggiato et al 2002;Clements et al 2004;Maiorano et al 2009). A relationship between the mycotoxin contamination of kernels and corn borer (Ostrinia nubilalis) incidence has been demonstrated in several studies even when using Bt transgenic maize (Clements et al 2003;Alma et al 2005). It appears that the presence of Cry1Ab protein in Bt maize does not guarantee that the fumonisin level will be kept down to a concentration which is not dangerous for human consumption if the season is favourable for the corn borer pest (Clements et al 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Therefore, fumonisins are strongly correlated with European corn borer (ECB, Ostrinia nubilalis) infection. It was observed that ears injured by second ECB generation larvae had a fumonisin B1 contamination level more than 10 times higher than that of healthy ears, while no significant differences for zearalenone and DON contents were observed (Alma et al, 2005). Insecticide application was successful in the control ECB incidence, and has significantly, but not completely, reduced fumonisin content.…”
Section: Management Of Mycotoxins In the Fieldmentioning
confidence: 94%